Acute Exposure to Normobaric Hypoxia Impairs Balance Performance in Sub-elite but Not Elite Basketball Players - Pojskić, Haris; Hanstock, Helen G.; Tang, Tsz-Hin; Rodríguez-Zamora, Lara (Frontiers in Physiology, 2021)
Although high and simulated altitude training has become increasingly popular training method, no study has investigated the influence of acute hypoxic exposure on balance in team-sport athletes. Therefore, the purpose of this study was to investigate whether acute exposure to normobaric hypoxia is detrimental to balance performance in highly-trained basketball players. Nine elite and nine sub-elite male basketball players participated in a randomized, single-blinded, cross-over study. Subjects performed repeated trials of a single-leg balance test (SLBT) in an altitude chamber in normoxia (NOR; ~ sea level) with FIO220.9% and PIO2 146.7-150.4 mmHg and normobaric hypoxia (HYP; ~3800 m above sea level) with FIO213.0% and PIO2 90.9-94.6 mmHg. The SLBT was performed three times: 15 min after entering the environmental chamber in NOR or HYP, then twice more interspersed by 3 min rest. Peripheral oxygen saturation (SpO2) and heart rate (HR) were recorded at four time-points: after the initial 15 minutes rest inside the chamber and immediately after each SLBT. Across the cohort, balance performance was 7.1% better during NOR than HYP (P<0.01, ηp2=0.58). However, the elite group’s performance was not impaired by HYP, whereas the sub-elite group performed worse in the HYP condition on both legs (DL: P=0.02, d=1.23; NDL: P=0.01, d=1.43). SpO2 was lower in HYP than NOR (P<0.001, ηp2=0.99) with a significant decline over time during HYP. HR was higher in HYP than NOR (P=0.04, ηp2=0.25) with a significant increase over time. Acute exposure to normobaric hypoxia detrimentally affected balance performance in sub-elite but not elite basketball players.